Represifisme, Beban Publik, dan Ekonomi Rakyat: Krisis Nilai di Tengah Kekerasan Negara - Rifki, Muchamad; Wahyudin, Wahyudin; Pujawa, Aneng Roehanah; Fauziyah, Nita; Juhara, Heri (Penerbit Widina, Widina Media Utama, 2025)
The wave of demonstrations in Indonesia from late August to early September 2025 reflected public unrest over social injustice, corruption, and weak state governance. The mass demonstrations that took place in various regions prompted a repressive response from security forces, including the use of tear gas, rubber bullets, mass arrests, and even loss of life. This study aims to analyze the crisis of values arising from the clash between the people's right to express their aspirations and state repression. The research method used a descriptive qualitative approach based on observations of literature, online news, and reports from human rights organizations. The results indicate that repression leads to a degradation of democratic values, justice, and humanity. Furthermore, the economic burden on the people is further burdened by the disruption of social and economic activities. This study emphasizes the importance of a humanistic approach in handling demonstrations to prevent further erosion of basic societal values.ABSTRAKGelombang demonstrasi di Indonesia pada akhir Agustus hingga awal September 2025 mencerminkan keresahan publik terhadap ketidakadilan sosial, korupsi, dan lemahnya tata kelola negara. Aksi massa yang berlangsung di berbagai daerah memunculkan respons represif dari aparat keamanan, termasuk penggunaan gas air mata, peluru karet, penangkapan massal, hingga jatuhnya korban jiwa. Penelitian ini bertujuan untuk menganalisis krisis nilai yang lahir dari benturan antara hak masyarakat untuk menyampaikan aspirasi dengan tindakan represif negara. Metode penelitian menggunakan pendekatan kualitatif deskriptif berbasis observasi literatur, berita daring, dan laporan lembaga HAM. Hasil kajian menunjukkan bahwa represifisme menimbulkan degradasi nilai demokrasi, keadilan, dan kemanusiaan. Selain itu, beban ekonomi rakyat semakin berat akibat terganggunya aktivitas sosial dan ekonomi. Penelitian ini menegaskan pentingnya pendekatan humanis dalam penanganan demonstrasi, agar nilai-nilai dasar kemasyarakatan tidak semakin tergerus.